HYDROLYSIS AND ELECTRICAL CONDUCTIVITY OF METHYLAMONIUM SULFAMATE AQUEOUS SOLUTIONS - R. E. Khoma (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2020)
The pH-metric, conductometric and spectrophotometric study of the acid-base and electrochemical properties of methylammonium sulfamate aqueous solutions (1·10-4 – 1·10-2 М) in the temperature range 293 – 313 K has been done. The increase in pH and molar conductivity of the studied solutions during their storage over time is explained by the hydrolytic decomposition of sulfamate anions with the formation of sulfate anions and ammonium cations. In the concentration range (0,1 – 1,0)·10-3 М, the degree of hydrolysis of sulfamate anions depends slightly on the initial salt content and reaches 100%. A further increase in the salt content results a directly proportional decrease in the hydrolysis degree. Limit molar conductivity values by Shydlovsky extrapolation are calculated. The influence of the initial concentration of methylammonium sulfamate on the electrochemical properties of aqueous solutions was revealed. The experimental values of the limit molar electrical conductivity of aqueous solutions obtained with an extrapolation of Shidlovsky with an initial concentrations of methylammonium sulfate (1,0 – 10,0)·10-3 М increase with increasing temperature from 293 to 308 K. For solutions with a higher concentration, the values of the limit molar electrical conductivity is independent on temperature and l0 equals 206±19 Om-1·sm2·mol-1. The activation parameters of the conductivity of the investigated solutions at 293 – 313 K were obtained. A relative decrease in the mobility of hydrogen ions in the test solutions was observed, comparable to the valve of the mobility during the transfer along the H-bonds of water. The negative values of ΔS# indicate that the atoms in the activated complexes are located more «compactly» than in the original systems, that is, in the formation of the activated complexes the number of rotational and oscillatory degrees of freedom decreases. The compensatory effects in the activation parameters of the molar electrical conductivity of aqueous solutions of methylammonium sulfamate in the temperature range 293 – 313K are indicated.